Problematika Membangun Pemahaman Konsep Geometri Transformasi Mahasiswa Pendidikan Matematika di Universitas Muhammadiyah Kotabumi Tahun Akademik 2019/2020 - Karsoni Berta Dinata (Eksponen, 2019)
Transformation geometry is one of the subjects in the curriculum structure of the Muhammadiyah Kotabumi University Mathematics Education Study Program taught in semester 4. One of the goals of learning transformation geometry is for students to comprehend transformation geometry in depth and be able to formulate concepts in a problem. Of course, to achieve this goal many problems are faced. This article seeks to conduct an objective descriptive analysis of the problems in building students' understanding of the geometry of transformation concepts based on the teaching experience of transformation geometry courses. Next we will try to find a strategy to overcome all problems in building understanding of the concept of transformation geometry.